PENGARUH PRODUKTIVITAS, DISIPLIN DAN KINERJA PEGAWAI TERHADAP BESARAN TUNJANGAN PERBAIKAN PENGHASILAN (TPP) (Studi Kasus Pada Aparatur Sipil Negara Sekretariat Daerah Kabupaten Sukoharjo) - qomariyah, nurul; Lestari, Sri Isfantin Puji; Triatmono, Agus (JURNAL ILMIAH EDUNOMIKA, 2025)
This research discusses the influence of employee productivity, discipline and performance on the amount of income improvement allowance (tpp). This research aims to explore and analyze the influence of productivity, discipline and employee performance on the amount of Income Improvement Allowance (TPP) at the Regional Secretariat of Sukoharjo Regency. The main focus of this research is to evaluate the extent to which these factors influence the amount of TPP received by employees, as well as to identify any inconsistencies or problems in implementing the performance appraisal system and providing TPP. The samples were selected using a random method or random sampling according to the specified sample size. The number of samples taken in this research was 50 respondents. The results of the research show that there is an influence of Productivity (X1) on the amount of Income Improvement Allowance (Y) for the State Civil Apparatus (ASN) of the Regional Secretariat of Sukoharjo Regency. There is an influence of Discipline (X2) on the amount of income improvement allowance (Y) at the State Civil Apparatus (ASN) of the Regional Secretariat of Sukoharjo Regency. There is an influence of Performance (X3) on the amount of income improvement allowance (Y) at the State Civil Apparatus (ASN) of the Regional Secretariat of Sukoharjo Regency. There is a joint influence of Productivity (X1), Discipline (X2) and Performance (X3) on the amount of income improvement allowance (Y) for the State Civil Apparatus (ASN) of the Regional Secretariat of Sukoharjo Regency. The most dominant variable influencing the amount of income improvement allowance (TPP) at the Sukoharjo Regency Regional Secretariat State Civil Apparatus (ASN) is Discipline (X2).Keywords: productivity, discipline, employee performance, amount of income improvement allowance (tpp).